Streptomyces endocoffea sp. nov. , an endophytic actinomycete isolated from Coffea arabica (L.) - Achararak Nammali; Chakapong Intaraudom; Pattama Pittayakhajonwut; Chanwit Suriyachadkun; Sarin Tadtong; Somboon Tanasupawat; Chitti Thawai (My University, 2021)
Abstract An aerobic, non-motile, Gram-stain positive actinomycete, designated strain CA3R110 T , was isolated from the surface-sterilised root of Coffea arabica L. collected from Lampang Province, Thailand. 16S rRNA gene sequence analysis indicated that strain CA3R110 T is a member of the genus Streptomyces and showed the closest similarities to Streptomyces rapamycinicus NRRL B-5491 T (99.1%), followed by S. iranensis HM 35 T (99.0%). Strain CA3R110 T contained LL -diaminopimelic acid in cell peptidoglycan, MK-9(H 6 ), and MK-9(H 8 ) as major menaquinone, iso -C 16:0, iso -C 15:0, C 16:0 as major fatty acids. Diphosphatidylglycerol, phosphatidylethanolamine, hydroxy-phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositolmannoside were detected in the cell. The chemotaxonomic characteristics possessed the typical properties of the genus Streptomyces . A low digital DNA–DNA hybridization (< 55.6%) and average nucleotide identity-blast (ANIb) (< 92.2%) values revealed that strain CA3R110 T could be distinguished from any known Streptomyces species. With the differences in phenotypic and genotypic data, strain CA3R110 T represents a novel species of genus Streptomyces , for which the name Streptomyces endocoffea sp. nov. is proposed. The type strain is CA3R110 T (= TBRC 11245 T = NBRC 114296 T ).
Keywords: Strain (injury); Diamino acid; Plant Disease Resistance and Genetics